1994
DOI: 10.1590/s0104-11691994000100007
|View full text |Cite
|
Sign up to set email alerts
|

Atitudes de profissionais de enfermagem em relação ao paciente queimado: elaboração e teste de fidedignidade de um instrumento

Abstract: Desenvolveu-se um instrumento de Medida de Atitudes dos Profissionais de enfermagem em relação ao Paciente Queimado. Cento e noventa e quatro (194) itens agrupados em subescalas, declarativos de atitudes favoráveis e desfavoráveis frente ao paciente queimado foram analisados quanto à validade aparente e de conteúdo. Após essa análise psicométrica, cento e setenta (170) itens compuseram a escala definitiva. O coeficiente de fidedignidade calculado pelo método da divisão por metades, variou de 0,61 a 0,82 para a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…* The heart is considered a body sense to influence the perception of other senses In this sense, a study (9) observed that the attitudes of the team can directly interfere in patients' adjustment to the admission process, they can also interfere in the cultural meaning of pain and in the care of the clienteles' pain complaints (7,10) . The studies indicate a critical/reflexive practice to improve interpersonal and care relations (7,10) .…”
Section: Discussionmentioning
confidence: 99%
“…* The heart is considered a body sense to influence the perception of other senses In this sense, a study (9) observed that the attitudes of the team can directly interfere in patients' adjustment to the admission process, they can also interfere in the cultural meaning of pain and in the care of the clienteles' pain complaints (7,10) . The studies indicate a critical/reflexive practice to improve interpersonal and care relations (7,10) .…”
Section: Discussionmentioning
confidence: 99%